Genres of rewriting in Second Temple Judaism scribal composition and transmission - Zahn, Molly M. 1979- (New York University of Cambridge ESOL Examinations, 2020)
A study of the many different ways ancient Jewish scribes changed, or rewrote, the sacred and authoritative traditions they inherited.
Description based on publisher supplied metadata and other sources
Keywords: Judaism-History-Post-exilic period, 586 B.C.-210 A.D; Authority-Religious aspects; Electronic books